2020
DOI: 10.1186/s12870-020-2282-0
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic characteristics and chloroplast ultrastructure of welsh onion (Allium fistulosum L.) grown under different LED wavelengths

Abstract: Background: The optimized illumination of plants using light-emitting diodes (LEDs) is beneficial to their photosynthetic performance, and in recent years, LEDs have been widely used in horticultural facilities. However, there are significant differences in the responses of different crops to different wavelengths of light. Thus, the influence of artificial light on photosynthesis requires further investigation to provide theoretical guidelines for the light environments used in industrial crop production. In … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 68 publications
(70 reference statements)
2
30
1
Order By: Relevance
“…In our research, we found that compared with W treatment, WB treatment appreciably promoted the growth of green onions, while WY and WG appreciably inhibited the growth of green onions (Table 1), which was inconsistent with the results in lettuce reported by Li and Kubota (2009). In addition, compared with the fullspectrum W light, monochromatic light (B, G, Y, and R) treatment appreciably inhibited the growth of green onions (Gao et al, 2020).…”
Section: Discussioncontrasting
confidence: 81%
“…In our research, we found that compared with W treatment, WB treatment appreciably promoted the growth of green onions, while WY and WG appreciably inhibited the growth of green onions (Table 1), which was inconsistent with the results in lettuce reported by Li and Kubota (2009). In addition, compared with the fullspectrum W light, monochromatic light (B, G, Y, and R) treatment appreciably inhibited the growth of green onions (Gao et al, 2020).…”
Section: Discussioncontrasting
confidence: 81%
“…Biomass is an important indicator of seedling quality. In this study, the seedling DW under RB was signi cantly greater than those under other treatments, which suggested that this spectrum was optimal because it promoted plant development and drove photosynthesis by increasing Chl a and total Chl contents in the seedlings [33,40]. Previous studies also found that mixed R and B light could promote fresh weight (FW) and DW in many other plant species, such as chrysanthemum, upland cotton and tomato [41][42][43].…”
Section: Discussionmentioning
confidence: 67%
“…The study elucidated unique responses including greatest fresh-to-dry mass ratio, greater leaf area, excessive stem extension, and flower initiation under the sun-simulated spectrum despite a 36% greater photosynthetic photon flux density (PPFD) in B:R treatments. Coinciding results were published by Gao and coworkers (2020), who tested the effects of white and different monochromatic (B, G, Y, R) LEDs on Welsh onions [ 40 ]. In addition to increased plant yield, net photosynthetic rate and photosynthetic efficiency were significantly higher under white light than under those of the monochromatic light treatments.…”
Section: Introductionmentioning
confidence: 67%